2021
DOI: 10.1089/thy.2020.0826
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Statement from the American Thyroid Association, the European Association of Nuclear Medicine, the European Thyroid Association, the Society of Nuclear Medicine and Molecular Imaging on Current Diagnostic and Theranostic Approaches in the Management of Thyroid Cancer

Abstract: Background: The American Thyroid Association (ATA), the European Association of Nuclear Medicine, the European Thyroid Association, and the Society of Nuclear Medicine and Molecular Imaging have established an intersocietal working group to address the current controversies and evolving concepts in thyroid cancer management and therapy. The working group annually identifies topics that may significantly impact clinical practice and publishes expert opinion articles reflecting intersocietal collaboration, conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 61 publications
2
47
0
6
Order By: Relevance
“…In a recent statement, the Martinique group advocates the additional use of pretherapeutic diagnostic whole body scans in selected patients in the intermediate-risk category (30). One argument for a diagnostic whole-body scan with 131 I prior to therapy might be staging for example from an M0 to a M1 status which may lead to a change in the treatment plan.…”
Section: Thyroglobulin Ultrasound and Diagnostic Whole Body Scan To Refine Rai Therapy Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent statement, the Martinique group advocates the additional use of pretherapeutic diagnostic whole body scans in selected patients in the intermediate-risk category (30). One argument for a diagnostic whole-body scan with 131 I prior to therapy might be staging for example from an M0 to a M1 status which may lead to a change in the treatment plan.…”
Section: Thyroglobulin Ultrasound and Diagnostic Whole Body Scan To Refine Rai Therapy Decisionsmentioning
confidence: 99%
“…One argument for a diagnostic whole-body scan with 131 I prior to therapy might be staging for example from an M0 to a M1 status which may lead to a change in the treatment plan. However, it should be emphasized that diagnostic 131 I scans with low activity even including SPECT/CT imaging have lower sensitivity than post therapy scans, the limitations are also addressed by the group (30). Agate et al showed in 545 low-and intermediaterisk patients, that less that 2% post-therapy scans showed distant metastases (31), which makes it obvious that only few patients may be "upgraded" by such imaging.…”
Section: Thyroglobulin Ultrasound and Diagnostic Whole Body Scan To Refine Rai Therapy Decisionsmentioning
confidence: 99%
“…DTC is biologically and functionally heterogeneous, with different molecular pathways impacting cancer cell biology. In particular, BRAF V600E mutation is associated with reduced expression of all thyroid-specific genes involved in iodine metabolism, resulting in variable decreased responsiveness to 131 I therapy (2). The clinical, pathologic, and molecular characteristics of DTC are summarized in Supplemental Table 1 (supplemental materials are available at http://jnm.snmjournals.org) (3).…”
Section: Epidemiology and Classificationmentioning
confidence: 99%
“…Intermediate-risk patients represent a heterogeneous group of patients, and their management is still under debate. RAI treatment should be planned according to risk factors and post-operative findings [ 105 ]. A longitudinal and observational study compared the outcomes of low and lower-intermediate risk (minimal extra-thyroid extension or ≤5 central compartment lymph node metastases) DTC patients undergoing either systematic or selective use of RAI treatment [ 106 ].…”
Section: Indications For the Use Of Radioactive Iodinementioning
confidence: 99%
“…At the present time, d-WBS is less frequently performed: post-operative administration of 131 I is mostly based on the surgical report, on prognostic indicators and on post-operative serum Tg level and neck US findings; additionally, the completeness of total thyroidectomy is improved, leaving in most patients only small remnants of non-tumoral thyroid tissue and in this condition the post-therapy WBS is frequently more informative than the d-WBS that is currently not routinely performed in many centers in low risk patients. A recent statement proposed that a d-WBS might be selectively performed in intermediate risk patients in the post-operative staging to guide, in addition to clinical and surgical data the decision of a therapeutic RAI administration and select a personalized patient-based activity [105]; however, in the absence of prospective data, the benefits afforded by the d-WBS remain uncertain. A randomized trial in lower-intermediate risk DTC patients (estimated risk of recurrence about 8%) comparing systematic RAI administration (3700 MBq) to a selective RAI administration based on post-operative rhTSH stimulated Tg, neck US and RAI d-WBS is ongoing in France (INTERMEDIATE trial, NCT04290663).…”
Section: Use Of Radioiodine For Diagnosismentioning
confidence: 99%